2003
DOI: 10.1007/s00056-003-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

Apical Root Resorption after Lingual Orthodontic Therapy

Abstract: The results suggest that lingual orthodontic therapy resulted in only slight root resorptions. Pronounced root shortenings were observed in some patients whose individual predisposition may constitute the main risk factor for the occurrence of root resorptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 18 publications
4
34
0
6
Order By: Relevance
“…Obwohl in der Literatur weitestgehende Einigkeit bezüglich der Tatsache herrscht, dass obere Inzisivi im Durchschnitt häu-figer und stärker von externen apikalen WR betroffen sind als andere Zähne [1,10,14,17,19,23,30,35,50,53,54], bleibt bisher unklar, warum diese lokale Häufung existiert.…”
Section: Methodsunclassified
See 2 more Smart Citations
“…Obwohl in der Literatur weitestgehende Einigkeit bezüglich der Tatsache herrscht, dass obere Inzisivi im Durchschnitt häu-figer und stärker von externen apikalen WR betroffen sind als andere Zähne [1,10,14,17,19,23,30,35,50,53,54], bleibt bisher unklar, warum diese lokale Häufung existiert.…”
Section: Methodsunclassified
“…This rose to 56% at the end of treatment. Generally speaking, the published values of RR frequency vary widely (18% -93%) [14,28,57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of Krieger et al, Fritz et al and Linge and Linge, all root and crown measurements were assessed by one examiner blinded in a stochastic sequence (11,29,30). To evaluate the pre-and post-treatment root length a symmetric cross was defined by two connecting lines: the first from the width of the incisal edge of the tooth to the apex, the second from the mesial and distal edge of cementoenamel-junction.…”
Section: Methodsmentioning
confidence: 99%
“…5 However, in most studies only a small percentage of severe and/ or moderate resorption was reported. 2,3,[6][7][8][9][10][11][12] In the literature, recommendations and protocols for radiographic evaluation of root resorption before and during orthodontic treatment are given, as well as guidelines for considerations in the treatment planning process. 13 Significant parameters regarding treatment approach and prevention of root resorption are the use of light and intermittent forces, 2,14 early orthodontic treatment timing, 4 treatment interruption/resting periods, 13 oral habits control, 15,16 and radiographic monitoring after 6 months of treatment (or 3 months when enhanced risk exists).…”
Section: Introductionmentioning
confidence: 99%